Transmission expansion planning - A multiyear PSO based approach considering load uncertainties - Manuel Costeira da Rocha (2013)
This paper describes a multiyear dynamic Transmission Expansion Planning, TEP, model to select and schedule along the planning horizon transmission expansion projects taken from a list supplied by the planner. The selection of the most adequate set of projects from this list is driven by the minimization of the investment plus operation costs while enforcing a number of constraints related with technical, financial and reliability issues. The developed approach also admits that nodal loads are modeled by triangular fuzzy numbers as a way to ensure obtaining more robust plans that is plans not only adequate for a deterministic set of future loads but plans that can accommodate load uncertainty. Finally, given the discrete nature of the problem, it was adopted a discrete version of the Evolutionary Particle Swarm Optimization algorithm, DEPSO, that proved very effective and shows good performance on several tests ran with the IEEE RTS system. (c) 2013 IEEE.